Probing Prompting Model to Improve Student Communication Skills in Civic Education Subjects - Khasanah, Uswatun (Journal of Elementary School Education, 2023)
This study aims to: 1) determine students' communication skills before applying the Probing Prompting Learning Model in Civics lessons for fifth grade students at SD N 101390 Batang Pane 1 in the 2022/2023 academic year, 2) determine students' communication skills after applying the Probing Prompting Learning Model in Civics lessons. fifth grade students of SD N 101390 Batang Pane 1 Academic Year 2022/2023, 3) improve students' communication skills in Civics material after applying the Probing Prompting learning method for fifth grade students of SD N 101390 Batang Pane 1 Academic Year 2022/2023. This study uses a Classroom Action Research approach. The data collection techniques in this study are observations and tests. The results showed that: 1) Through the Probing Prompting learning model there was an increase in the communication skills of fifth grade students at SD Negeri 101390 Batang Pane 1 in Civics learning. 2) Students' communication skills were obtained through the application of the Probing Prompting learning model, namely the average score of students' communication skills in the first cycle was 76.88 and increased by 94.75 in the second cycle. The Probing Prompting learning model has been implemented according to the learning scenario in class V at SD Negeri 101390 Batang Pane 1.